Predictive potential of macrophage migration inhibitory factor (MIF) in patients with heart failure with preserved ejection fraction (HFpEF) - Peter Luedike; Georgios Alatzides; Maria Papathanasiou; Martin Heisler; Julia Pohl; Nils Lehmann; Tienush Rassaf (European Journal of Medical Research, 2018)
Abstract Background Prognostication in heart failure with preserved ejection fraction (HFpEF) is challenging and novel biomarkers are urgently needed. Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine that plays a crucial role in cardiovascular and various inflammatory diseases. Whether MIF is involved in HFpEF is unknown. Methods and results Sixty-two patients with HFpEF were enrolled and followed up for 180 days. MIF plasma levels as well as natriuretic peptide (NP) levels were assessed. High MIF levels significantly predicted the combined end-point of all-cause death or hospitalization at 180 days in the univariate analysis (HR 2.41, 95% CI 1.12–5.19, p = 0.025) and after adjustment for relevant covariates in a Cox proportional hazard regression model (HR 2.35, 95% CI 1.05–5.27, p = 0.0374). Furthermore, MIF levels above the median were associated with higher pulmonary artery systolic pressure (PASP) as assessed by echocardiography (PASP 31 mmHg vs 48 mmHg in the low- and high-MIF group, respectively, p = 0.017). NPs significantly correlated with MIF in HFpEF patients (BNP p = 0.011; r = 0.32; NT-proBNP p = 0.027; r = 0.28). Conclusion MIF was associated with clinical outcomes and might be involved in the pathophysiology of pulmonary hypertension in patients with HFpEF. These first data on MIF in HFpEF should stimulate further research to elucidate the role of this cytokine in heart failure. Trial registration NCT03232671